2011
DOI: 10.5090/kjtcs.2011.44.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Cox-maze IV Procedure Using Bipolar Irrigated Radiofrequency Ablation and Cryothermy in Valvular Heart Disease

Abstract: BackgroundWe evaluated the efficacy of Cox-maze IV procedure using bipolar irrigated radiofrequency ablation and cryothermy in chronic atrial fibrillation associated with valvular heart disease.Material and MethodsFrom November 2005 to June 2009, ninety four patients have undergone valvular heart surgery with Cox-maze IV procedure. Preoperative duration of atrial fibrillation was 7.6±6.5 years and follow-up duration was 22.7±12.3 months.ResultsThere were two (2.1%) postoperative deaths not related to maze proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
0
12
0
3
Order By: Relevance
“…In our study, age, duration of AF, and postoperative LA dimension were identified as risk factors for early conversion (at postoperative 6 months), but not for sustained SR during the mid-term follow-up period. The risk factors for early conversion (at postoperative 6 months) were also described in a previous report [17]. …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In our study, age, duration of AF, and postoperative LA dimension were identified as risk factors for early conversion (at postoperative 6 months), but not for sustained SR during the mid-term follow-up period. The risk factors for early conversion (at postoperative 6 months) were also described in a previous report [17]. …”
Section: Discussionmentioning
confidence: 97%
“…Although the LA dimension and age were not predictive factors of recurrent AF in the mid-term follow-up, they were significant predictors of early SR conversion. Previous reports [17,18] have demonstrated that age is an important factor for SR conversion after the maze operation in patients with giant LA and a more aggressive surgical approach is required in younger patients with giant LA for more favorable results. Many reports [17,19] readily ruled the maze procedure a success or failure at the postoperative 3rd month or 6th month, but many cases for which operative success had been determined then experienced delayed recurrence of AF [19].…”
Section: Discussionmentioning
confidence: 99%
“…Kim та співавт. з тривалістю спостереження 10 років взяли участь 540 пацієнтів, які перенесли хірургічну корекцію мітральної вади (пластика або протезування) [16]. У частини пацієнтів проводили хірургічну абляцію ФП із застосуванням холодової (n = 185) та мікрохвильової енергії (n = 10).…”
Section: методи лікування фібриляції передсердь у пацієнтів з клапаннunclassified
“…In addition, age is deemed to be an independent predictor of stroke in patients with AF [9]. Age of≥70 years is frequently accompanied by multiple comorbidities, and is a significant risk factor associated with worse postoperative results [10][11][12][13]. Thus, whether concomitant BRFA should be performed in elderly patients is controversial.…”
Section: Introductionmentioning
confidence: 99%